A synthetic biological secondary metabolite, Lycogenâ¢, produced and extracted from Rhodobacter sphaeroides WL-APD911 in an optimizatioal scale-up strategy - Cheng-Chin Wang; Shi-Ying Huang; Shu-Hung Huang; Zhi-Hong Wen; Jyun-Ying Huang; Wen-Sheng Liu; Hui-Min David Wang (Food Science and Human Wellness)
The optimization of fermentation medium is important for synthetic biological secondary metabolite productions. The effect of rotation speed, inoculum amount, and medium supplements on the cell growth and Lycogenâ¢ secretion of photobacterium Rhodobacter sphaeroides WL-APD911 was evaluated. The results reveal that a higher rotational speed exhibit a higher cell density, and the increasing in the amount of inoculum amount show a slight augment on the growth of R. sphaeroides WL-APD911.In the case of nitrogen sources adding, Lycogenâ¢ production was achieved with a 0.5Â mM l-lysine supplementation. Moreover, the attention of Tween 80 presented a tremendous increase in the secondary metabolite. Response surface methodology (RSM) exhibited the optimization of medium supplements for Lycogenâ¢ invention is accomplished at molasses concentration of 10Â g/L, yeast extract concentration of 40Â g/L, 0.3% Tween 80 and NaCl concentration of 5Â g/L, respectively. Further, the batch fermentation is carried out in both 5Â L and 20Â L fermentors to study the scale-up process factors to be adopted. At a 20Â L fermentor, Lycogenâ¢ yields under the optimal culture condition are over 2 times than in the shake flask. The present results provide the Lycogenâ¢ optimal culture mediums, scale-up procedures and efficient extractions from R. sphaeroides WL-APD911. Keywords: Rhodobacter sphaeroides WL-APD911, Lycogenâ¢, Response surface methodology (RSM), Ferementation